El derecho a la comunicación en la prensa ecuatoriana ¿logro o deuda pendiente? caso de estudio: la cobertura informativa sobre manifestaciones en Venezuela y Ecuador 2019 - Castañeda Suárez, Ana Graciela (2021)
In order to verify the guarantee of the Right to Communication in the Ecuadorian press, it examines how the newspaper El Comercio reported two protest events against two governments whose relationship with the Establishment, or the established power, is opposite: the governments of Ecuador and Venezuela in 2019. The results are compared with the provisions of Article 22 of the Organic Law on Communication, in relation to the obligation of the press to contrast sources on the subject collected and are then examined in the light of the third filter of the Propaganda Model developed by Herman and Chomsky, referring to the sources of the news. It is concluded that there is a departure from the guarantee of the Right to Communication and the need for a model that distributes media property more equitably than the current one, in order to diversify the voices that are part of the discussion on issues of social importance, which allow the exercise of a well-informed and therefore full and legitimate democracy.